Peningkatan Keterampilan Membaca dengan Media Kartu Kata dan Pembelajaran Berdiferensiasi pada Siswa Kelas I SDN Jajartunggal III/452 Surabaya - Alifah Isro’ini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The study entitled Improving reading skills with Word Card Media and differentiated learning in first grade students of SDN Jajartunggal III / 452 Surabaya is based on the students who entered the first grade have different reading skills. There are those who already belong to the category of want, mamu, and can read. The research aims to improve students ' reading skills by focusing on the utilization of Recycle-based learning media around students. This is because the manufacture of word cards comes from waste paper in the administrative staff room at school. This study is a type of qualitative descriptive research, the problem will be described through words from specific to general, the process of collecting and analyzing data is done in a narrative manner. Data collection techniques in research at SD Negeri Jajartunggal III / 452 Surabaya conducted by observation techniques, interviews and documentation studies. In this study apply several stages of planning, implementation of action, observation, and reflection. The results of this study show that it is concluded that the media word cards from waste paper and using differentiated learning methods, as a form of Independent curriculum, can improve the reading skills of first grade students at SDN Jajartunggal III/452 so that this will also improve student learning outcomes in the classroom.